Pericardial- Rather than Intramyocardial Fat Is Independently Associated with Left Ventricular Systolic Heart Function in Metabolically Healthy Humans - Wolf, Peter; Winhofer, Yvonne; Smajis, Sabina; Jankovic, Draženka; Anderwald, Christian-Heinz; Trattnig, Siegfried; Luger, Anton; Krebs, Michael; Krššák, Martin (PloS one, 2016)
Obesity is a major risk factor to develop heart failure, in part due to possible lipotoxic effects of increased intramyocardial (MYCL) and/or local or paracrine effects of pericardial (PERI) lipid accumulation. Recent evidence suggests that MYCL is highly dynamic and might rather be a surrogate marker for disturbed energy metabolism than the underlying cause of cardiac dysfunction. On the other hand, PERI might contribute directly by mechanic and paracrine effects. Therefore, we hypothesized that PERI rather than MYCL is associated with myocardial function. To avoid potential confounding of metabolic disease 31 metabolically healthy subjects (age: 29±10yrs; BMI: 23±3kg/m2) were investigated using 1H-magnetic resonance spectroscopy and imaging. MYCL and PERI, as well as systolic and diastolic left ventricular heart function were assessed. Additionally, anthropometric data and parameters of glucose and lipid metabolism were analyzed. Correlation analysis was performed using Pearson's correlation coefficient. Linear regression model was used to show individual effects of PERI and MYCL on myocardial functional parameters. Correlation analysis with parameters of systolic heart function revealed significant associations for PERI (Stroke Volume (SV): R = -0.513 p = 0.001; CardiacIndex (CI): R = -0.442 p = 0.014), but not for MYCL (SV: R = -0.233; p = 0.207; CI: R = -0.130; p = 0.484). No significant correlations were found for E/A ratio as a parameter of diastolic heart function. In multiple regression analysis CI was negatively predicted by PERI, whereas no impact of MYCL was observed in direct comparison. Cardiac fat depots impact left ventricular heart function in a metabolically healthy population. Direct comparison of different lipid stores revealed that PERI is a more important predictor than MYCL for altered myocardial function.